Modeling Jack Pine ( Pinus banksiana ) Foliage Density Distribution - Robert Schneider; Mathieu Fortin; Frank Berninger; Chhun-Huor Ung; D. Edwin Swift; S.Y. Zhang (Forest Science, 2011)
The vertical distribution of foliage biomass is important because it is associated with photosynthesis and is closely related to some wood quality attributes such as branch diameter and sapwood content. In this article we propose a model to predict foliage biomass distribution within the crown for jack pine trees in Eastern Canada. This model has two parts. The first one distinguishes the proportion of nodal (formed at the end of each yearly shoot) and internodal (formed during the growing season) foliage biomass. The second part of the model predicts the distribution of the biomass depending on the type of foliage (nodal or internodal). This second part is based on a two-parameter beta cumulative distribution function (cdf). The parameterization of this cdf was performed using a mixed-effects nonlinear regression. The proportion of foliage biomass found in the nodal whorls is proportional to dbh and age and inversely proportional to total height. The distribution of the foliage biomass in the nodal whorls is dependent only on tree-level variables whereas the internodal foliage biomass is influenced by both tree- and stand-level variables. The internodal foliage biomass maximum is closer to the crown base than that of nodal foliage biomass. Decomposing the distribution into whorl types leads to a better description of crown characteristics.

A stand dynamic model for red pine plantations with different initial densities - Shusheng Li; Qingyu Hao; Edwin Swift; Charles P.-A. Bourque; Fan-Rui Meng (New Forests, 2011)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Combining carbon sequestration objectives with timber management planning - Fan-Rui Meng; Charles P.-A. Bourque; Steven P. Oldford; D. Edwin Swift; Helen C. Smith (Mitigation and Adaptation Strategies for Global Change, 2003)